Surgical feed ligation performed in 22 year old female with scalp arteriovenous malformation - Santhiadi, Nyoman Gde Trizka; Semadi, I. Nyoman (International Journal of Research in Medical Sciences, 2019)
Scalp arteriovenous malformation (AVM) are rare conditions that usually need surgical treatment. Its management is difficult because of its high shunt flow, complex vascular anatomy, and possible cosmetic complication. The etiology of scalp AVM may be spontaneous or traumatic. This vascular lesion present as scalp lump or a mass, grotesque, pulsatile mass with a propensity to massive haemorrhage. Various treatment option that have been adopted to treat these lesions include surgical excision, ligation of feeding vessel, trans arterial and transvenous embolization, injection of sclerosant into the nidus and electro thrombosis. A 22-years-old-female referred to cardiothoracic division with a 10 years history of a large fronto-parietal pulsatile reddish soft mass, progressively increasing in size, measuring about 15x6x2 cm, ulcerated area; without any symptoms and history of trauma. Three-dimensional CT angiography demonstrated a mass that was completely within the scalp and prominent vascular that was completely within the scalp and was not associated with bone or periosteum. The feeding arteries were originated from angular artery, supratrochlear artery, left and right superficial temporal artery. Surgical excision and ligation of feeding vessel was performed without complication. With pre-operative appropriate surgical planning, scalp AVM can be excised safely without any major complication. Though some cases may be treated with percutaneous or endovascular embolization, surgery remains the treatment of choice. In the event of scalp ulceration and haemorrhage, total excision is the only option.